The Baloch language: A brief sketch of its morphology - sabir, Pro,Dr. Abdul Razzaq (Hanken, 2009)
The aim of this paper is to discuss the dialect of the Balochi language its official and educational status in the education intuition and to take a glance over the written history of the Balochi language. The phonological and morphological system of the Balochi language will be focused to point out the grammatical system of the Balochi language.